Ilha de Santana e Alto de Santa Rita: a produção do espaço a partir do turismo em Caicó e Santa Cruz - RN - Silvino, Marluce (2012)
Tourism is an activity that uses the spatial objects and also produces and because it creates an economic activity areas for leisure. So for this to occur itdoes need a space reorganized, with infrastructure to receive visitors. And in the process of construction / reconstruction of tourist destination the state comes as a precursor, creating public policies that tourism can develop. Thus, this paper examines the transformation process by which the spaces are aiming to become tourist, and what changes occur in socio-spatial dynamic of the city in which this activity is inserted. The spatial area of study refers to the Alto de Santa Rita, Santa Cruz and the Isla de Santana Tourist Complex in Caicó both in Rio Grande do Norte. The reconstruction of the Island de Santana did not occur randomly, in order that the spatial changes were performed to meet the demand for which Caicó had to perform his greatest social and religious event, the Feast of Santana, which occurs since its colonization in year 1748 and also the Carnival these two events being considered as a strong tourist attraction of the city. And the Santa Rita High was built in order to enter the city of Santa Cruz in the script of religious tourism of the state through the devotion of the patron. The Dissertation isstructured in five parts, the first refers to the introduction of the work, while the second examines how tourism wound to the Rio Grande do Norte and internalizesthe third part deals with the spaces for tourism in these cities, the the fourthidentifies as the symbolism of these spaces influence the transformation and the latter reveals how these spaces affect the socio-economic structure of cities across the events